Hypoxia regulates GR function through multiple mechanisms involving microRNAs 103 and 107. (1st December 2020) - Yang, Nan; Berry, Andrew; Sauer, Carolin; Baxter, Matthew; Donaldson, Ian J.; Forbes, Karen; Donn, Rachelle; Matthews, Laura; Ray, David
Abstract: Glucocorticoids (Gcs) potently inhibit inflammation, and regulate liver energy metabolism, often acting in a hypoxic environment. We now show hypoxic conditions open a specific GR cistrome, and prevent access of GR to part of the normoxic GR cistrome. Motif analysis identified enrichment of KLF4 binding sites beneath those peaks of GR binding exclusive to normoxia, implicating KLF4 as a pioneer, or co-factor under these conditions. Hypoxia reduced KLF4 expression, however, knockdown of KLF4 did not impair GR recruitment. KLF4 is a known target of microRNAs 103 and 107, both of which are induced by hypoxia. Expression of mimics to either microRNA103, or microRNA107 inhibited GR transactivation of normoxic target genes, thereby replicating the hypoxic effect. Therefore, studies in hypoxia reveal that microRNAs 103 and 107 are potent regulators of GR function. We have now identified a new pathway linking hypoxia through microRNAs 103 and 107 to regulation of GR function. Highlights: Oxygen tension profoundly affects glucocorticoid (Gc) action. Gc target genes and regulatory elements are sensitive to oxygen tension. MicroRNAs 103 and 107 mediate the hypoxic regulation of Gc action. Hypoxia does not affect Gc receptor (GR) expression, modification or trafficking.